The future of oilseeds: climate change expected to negatively impact canola more than camelina - Quinlan, Gabriela; Goslee, Sarah (Frontiers in Agronomy, 2025)
IntroductionClimate change is expected to alter environmental suitability for crops. In the United States, the Northern Great Plains (NGP), a primary production area for many crops including oilseeds, is at particular risk for decreasing cropland suitability under climate change. While canola (Brassica napus L.) has historically dominated oilseed production in the NGP, camelina (Camelinasativa L.) has been suggested as a potential climate-smart oilseed crop for the future due to agronomic attributes including drought tolerance, low input requirements, and cold hardiness.MethodsIn this study, we examine the viability of both camelina and canola under future climate scenarios by first defining theircurrent environmental niche and then projecting their potential distribution under two different carbon emission scenarios.ResultsWhile both crops are currently grown primarily in the NGP, we found that they have distinct spatial and environmental ranges, and that these ranges are largely consistent with what is described in the literature about their differing biological niches. We also find that under future climate change scenarios, environmental suitability for both crops is projected to decrease, though more so for canola.DiscussionThis study helps to identify specific regions that may experience shifts (positive or negative) in environmental suitability for growing canola and camelina, but more broadly sheds light on the nonstationary and shifting range suitability that might be expected for crops under climate change.